2016
DOI: 10.2174/1874210601610010347
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Hydrogel Scaffold and Fibroblast Growth Factor-2 Accelerate Periodontal Healing of Class II Furcation Defects in Dog

Abstract: Objective:Collagen hydrogel scaffold exhibits bio-safe properties and facilitates periodontal wound healing. However, regenerated tissue volume is insufficient. Fibroblast growth factor-2 (FGF2) up-regulates cell behaviors and subsequent wound healing. We evaluated whether periodontal wound healing is promoted by application of collagen hydrogel scaffold in combination with FGF2 in furcation defects in beagle dogs.Methods:Collagen hydrogel was fabricated from bovine type I collagen with an ascorbate-copper ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Collagen gels together with FGF-2 treatment provided higher survival of embedded endothelial cells and enhanced vessel branching from embedded vessel fragments (Satake et al 1998 ; Nicosia et al 2005 ). Collagen hydrogels loaded with FGF-2 were used before incorporated into collagen sponges in periodontal wound healing and provided early ingrowth of vessel-like structures besides promoting healing in different tissue types (Momose et al 2016 ). In the light of these studies, collagen hydrogels can be a useful tool for providing an extracellular matrix for endothelial cell proliferation and migration, as well as a modifiable platform for delivering angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen gels together with FGF-2 treatment provided higher survival of embedded endothelial cells and enhanced vessel branching from embedded vessel fragments (Satake et al 1998 ; Nicosia et al 2005 ). Collagen hydrogels loaded with FGF-2 were used before incorporated into collagen sponges in periodontal wound healing and provided early ingrowth of vessel-like structures besides promoting healing in different tissue types (Momose et al 2016 ). In the light of these studies, collagen hydrogels can be a useful tool for providing an extracellular matrix for endothelial cell proliferation and migration, as well as a modifiable platform for delivering angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…After gaining polarity, both groups maintained it until day 7, which suggested that this model can maintain maturity until at least day 7 (consistent with the PCR result). FGF-2 is an important growth factor that enhances PDL regeneration (Momose et al, 2016). Both PN and PF groups showed similar increase and decrease patterns for FGF-2 and OCN , but without statistically significant differences under most circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MB-MSCs reduce apoptosis in granulosa cells and fibrosis of the ovarian interstitium, thereby improving folliculogenesis and rescuing overall ovarian function in an animal model of POF [58, 59], including restoring fertility [60]. In addition, Wang et al demonstrated that MB-MSCs produced a high level of fibroblast growth factor 2, which enhanced cell survival, proliferation, and function to repair tissue damage [61, 62]. Furthermore, Yan et al indicated that MB-MSCs reduced granulosa cell apoptosis and improved ovarian functions in mice by downregulating Gadd45b protein expression (a stress sensor whose effects are mediated via physical interactions with other cellular proteins implicated in cell cycle regulation) and upregulating cyclinB1 and CDC2 (regulators of the G2/M transition in mammalian cells) [6366].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%